Diskretni časovni kristali - Gnidovec, Andraž (Matrika, 2017)
Introduced here are concept of spontaneous discrete time translation symmetry breaking and definition of discrete time crystals. Challenges facing the idea and conditions for their realization are described. A model and an experiment are also presented along with their respective results.
Keywords: discrete time crystals; diskretni časovni kristali; modeli; models; numerical analysis; numerična analiza; rigidity; rigidnost; spontan zlom simetrije; spontaneous discrete time translation symmetry breaking